How to reduce food waste in public catering units? : a case study at twelve school canteens in Sala municipality, Sweden - Tromp, Malou (SLU/Dept. of Energy and Technology, 2021)
In developed countries, food is to a significant extend wasted at the consumption stage, meaning that it is discarded even if it is still suitable for human consumption. The further along the supply chain food is wasted, the more resources are lost and the higher the environmental impact is. Therefore, it is important to find ways to reduce food waste at a consumer level. In literature, different interventions are suggested to reduce food waste. However, there are not many studies that have quantified the impact of introducing these kinds of interventions. This study assesses the effect of food waste reduction interventions in public catering units in Sala municipality to see if they have the desired reduction effect. The interventions researched in this study are: “tasting spoon”, “plate waste tracker”, “awareness campaign” and “demand forecasting”. To assess the effects of the interventions the levels of food waste, after implementing the interventions, are compared to previous food waste levels. To verify the effect a control group, who did not take part in any interventions, is used. In addition, a survey is conducted to verify the quantification results, assess the correlation between the amount of waste per portion and the number of actions taken to reduce food waste and identify potential areas of improvement for the studied catering units. The results indicate that most of the public catering units where an intervention was introduced, had the desired reduction effect. However, there may be other factors that have influenced the reduction in food waste. Besides, some catering units have a misconception about where in their production process they produce most food waste and overestimate the number of guests they have daily. These misconceptions may cause catering units to focus on the wrong problem and/or generate more food waste. This study is a good basis for how the effect of introducing interventions for reducing food waste can be quantified and examined. With some improvements to the method, this may become a helpful tool for municipalities and catering units to examine which interventions are most viable for implementation.